THE EFFECT OF USING VIDEO MEDIA IN SKILLLABORATORY FOR STUDENT’S KNOWLEDGE AND SKILL IN MANAGING SHOULDER DYSTOCIA ATUBUDIYAH INDONESIA UNIVERSITY - Ulfa Farrah Lisa (JOURNAL OF HEALTHCARE TECHNOLOGY AND MEDICINE, 2015)
Shoulder dystocia is one of the most problematic obstetric causes which is strongly associated with fetal morbidity and mortality. Health providers should be prepared to deal with this obstetrics emergency. Qualified midwives are generated by educational institutions which attach to science development, information technology and regulation. One of them is skill laboratory during education with video. Laboratory activities using methods and appropriate learning media and varied will lead the students to the formation of skills and creativity in receiving knowledge.The research method was a quasiexperimental design with control group design. Subjects were students of fourth semester at Diploma III of Midwifery of U'BudiyahIndonesia University. Total sample was 32 people. Total population was used as technique of sampling. The analysis used univariate, bivariate analysis with the Mann Whitney test and t test and multifariate analysis using manova test with a significance level of 0.05.The results showed an increase of knowledge of the treatment group from 76,7 to 86,7, and in the control group 66,7 to 80, statistically significantly different (p=0.001).  Increase of skill of the treatment group from 50,8 to 90, and in the control group 48,6 to 75,5, statistically significantly different (p<0.001). Media video effect simultaneously on the knowledge and skills in the treatment groups (p <0.001). The percentage increase of 89.16% in the treatment group and the control group 62.44%.The percentage increase of 89.16% in the treatment group and the control group 62.44%.Conclusion results of the research, knowledge and skills of student about shoulder dystocia are higher on the given media video group compared to the control group. Keywords: video media, knowledge, skills, managing shoulder dystocia.